Manajemen Kurikulum Merdeka (Studi Multi Situs Di SMPN 3 Katingan Hulu dan SMPN 4 Katingan Hulu) - Kristian Hengki; Ahmad Suriansyah; Aslamiah Aslamiah (Universitas Negeri Malang, 2020)
Abstract: This study aims to describe curriculum management in the implementation of the Merdeka Curriculum through a multi-site study at SMPN 3 and SMPN 4 Katingan Tengah. The focus of the research includes school principals' policies, teacher empowerment, and school partnerships. A qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. The findings reveal that both schools successfully implemented the Merdeka Curriculum in an adaptive and contextual manner. School principals acted as instructional leaders, both visionary and facilitative, by encouraging innovation, academic supervision, and collaborative reflection with teachers. Teachers were empowered as primary designers and implementers of learning through training, collaboration, and the development of teaching materials based on local potential. The use of technology and professional learning communities supported ongoing teacher development. Strategic partnerships with various stakeholders, including community leaders, local entrepreneurs, religious institutions, and government agencies, strengthened the curriculum implementation. These collaborations supported contextual learning, character education, and community empowerment within the school environment.The study concludes that the synergy between strong school leadership, empowered teachers, and active partnerships is the key to successful curriculum management based on the Merdeka Curriculum. These findings provide implications for educational policy development, school capacity building, and teacher professional development in regions facing geographical and socio-cultural challenges. Keywords: management, curriculum, merdeka, teacher empowerment, partnership Abstrak: Penelitian ini bertujuan untuk mendeskripsikan manajemen kurikulum dalam implementasi Kurikulum Merdeka melalui studi multi situs di SMPN 3 dan SMPN 4 Katingan Tengah. Fokus penelitian mencakup kebijakan kepala sekolah, pemberdayaan guru, dan kemitraan sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa kedua sekolah mampu mengimplementasikan Kurikulum Merdeka secara adaptif dan kontekstual. Kepala sekolah berperan sebagai pemimpin pembelajaran yang visioner dan fasilitator, mendorong inovasi, supervisi akademik, serta refleksi bersama guru. Guru diberdayakan sebagai perancang dan pelaksana utama pembelajaran melalui pelatihan, kolaborasi, serta pengembangan perangkat ajar berbasis potensi lokal. Pemanfaatan teknologi dan komunitas belajar menjadi bagian penting dalam mendukung profesionalisme guru. Kemitraan strategis dengan berbagai pihak, seperti tokoh masyarakat, UMKM, lembaga keagamaan, dan instansi pemerintah, turut memperkuat pelaksanaan kurikulum. Kemitraan ini mendukung pembelajaran kontekstual, pendidikan karakter, dan pemberdayaan komunitas sekolah. Penelitian ini menyimpulkan bahwa sinergi antara kepemimpinan kepala sekolah, pemberdayaan guru, dan penguatan kemitraan merupakan kunci keberhasilan manajemen kurikulum berbasis Kurikulum Merdeka. Temuan ini memberikan implikasi bagi pengembangan kebijakan pendidikan, penguatan kapasitas sekolah, dan pengembangan profesional guru di daerah dengan tantangan geografis dan sosial budaya. Kata kunci: manajemen, kurikulum, kurikulum merdeka, pemberdayaan guru, kemitraan